Predicting CMEs Using ELEvoHI With STEREO‐HI Beacon Data - Maike Bauer; Tanja Amerstorfer; Jürgen Hinterreiter; Andreas J. Weiss; Jackie A. Davies; Christian Möstl; Ute V. Amerstorfer; Martin A. Reiss; Richard A. Harrison (Space Weather)
Abstract Being able to accurately predict the arrival of coronal mass ejections (CMEs) at Earth has been a long‐standing problem in space weather research and operations. In this study, we use the ELlipse Evolution model based on Heliospheric Imager (ELEvoHI) to predict the arrival time and speed of 10 CME events that were observed by HI on the STEREO‐A spacecraft between 2010 and 2020. Additionally, we introduce a Python tool for downloading and preparing STEREO‐HI data, as well as tracking CMEs. In contrast to most previous studies, we use not only science data, which have a relatively high spatial and temporal resolution, but also lower‐quality beacon data, which are—in contrast to science data—provided in real‐time by the STEREO‐A spacecraft. We do not use data from the STEREO‐B spacecraft. We get a mean absolute error of 8.81 ± 3.18 hr/59 ± 31 km s−1 for arrival time/speed predictions using science data and 11.36 ± 8.69 hr/106 ± 61 km s−1 for beacon data. We find that using science data generally leads to more accurate predictions, but using beacon data with the ELEvoHI model is certainly a viable choice in the absence of higher resolution real‐time data. We propose that these differences could be minimized if not eliminated altogether if higher quality real‐time data were available, either by enhancing the quality of the already available data or coming from a new mission carrying a HI instrument on‐board.